History, histories and historians in land reform: an insider's account. - Hassan, Asma (University of the Witwatersrand. History Workshop., 1999)
Those engaged in the South African Land Reform policy have invoked South Africa's contested history. Different histories impact policy formation and implementation. Historians have been employed by Governmental and non-governmental organisations involved in the Land Reform Programme. The paper offers personal impressions of the use and abuse of history and historians in the Land Reform Programme
Paper presented at the Wits History Workshop: Forging the links between historical research and the policy process, 18-19 September 1999.
Keywords: Land reform. South Africa; Land reform. South Africa. Historians; Land tenure. South Africa. Policy